Learning Speaking with Bahlul: Designing Communicative Instructional Materials from the Series "Bahlul A'qalul Majanin" for Islamic Boarding School Students - Sakinah, Naila; Bakhiet, Bakri Muhammad; Chamidah, Dewi (Abjadia : International Journal of Education, 2025)
This study aims to design and validate Arabic speaking instructional materials based on authentic dialogues from the television series Buhlul A‘qalul Majanin, integrated with digital learning platforms. The research subjects were students at Al-Kautsar Islamic Boarding School in Kraksaan, Probolinggo, who lacked standardized instructional materials and experienced challenges in developing their speaking skills. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instructional product developed, titled “كَلِّمْنِي يَا بَهْلُوْل!” (Speak to Me, Buhlul!), was designed thematically and communicatively, supported by interactive, digitally accessible features. Expert validation results indicated that the instructional material was highly feasible, scoring an average of 83% from the content expert and 91% from the media expert. The product was implemented with 20 students, showing improved engagement and speaking performance. The student response questionnaire also indicated a very high level of satisfaction, with an average score of 91 out of 100, reflecting strong acceptance and engagement. Furthermore, the results of the pre-test and post-test showed a significant improvement, with the average score increasing from 53.55 to 85.1. The n-Gain score indicated moderate to high learning gains.These findings suggest that the developed material is both relevant and effective for enhancing Arabic speaking skills in a pesantren (Islamic boarding school) context, particularly one supported by digital learning environments.